2020
DOI: 10.1021/acs.est.9b06191
|View full text |Cite
|
Sign up to set email alerts
|

Fast Evolution of Sulfuric Acid Aerosol Activated by External Fields for Enhanced Emission Control

Abstract: Sulfuric acid aerosol (SAA) can considerably deteriorate air visibility, which poses a threat to human health. Pretreatment methods that enlarge SAA sizes are crucial to enhanced emission control from industrials. This study provides an insight into SAA growth in terms of aerosol dynamics simulation and growth experiments under simulated flue gas conditions. Results show that SAA growth dynamics are dominated by coagulation and condensation mechanisms for small and large aerosols, respectively. The two mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…A generator was installed to produce SO 3 by SO 2 catalytic oxidation. 37,38 The generator was maintained at approximately 683 K to promote SO 3 conversion efficiency. Afterward, the gas entered the absorber with CO 2 /SO 2 /SO 3 mixed.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A generator was installed to produce SO 3 by SO 2 catalytic oxidation. 37,38 The generator was maintained at approximately 683 K to promote SO 3 conversion efficiency. Afterward, the gas entered the absorber with CO 2 /SO 2 /SO 3 mixed.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…To avoid the condensation of water vapor in the measurement system, the probe was heated to 423 K with the sampling line heated to 393 K. The concentration of SO 3 was converted based on the concentration of SO 2 at the inlet of the generator, with the conversion efficiency from SO 2 to SO 3 supposed to be nearly 100% since no residual SO 2 could be detected at the exit of the generator. 29,37,38 ■ RESULTS AND DISCUSSION Aerosol Formation Inhibition. Inhibiting the formation of aerosols in the absorber is the most direct way to reduce solvent loss.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The escaping particles carried some charges (Huang and Chen, 2002). The charge amount of the escaping particle can be even higher than that of the collected ones because the former resided a long time and were close to the discharge electrode (Yang et al, 2020). The charging characteristics of the escaping particles are fundamental for the coupling of WESP between other devices.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Researchers have suggested that enlarging the particle-size is a feasible method for increasing the efficiency of fine-particle-removal. , Additionally, it is possible to achieve particle growth in high supersaturation by optimizing the water vapor condensation process on the particle surface and the agglomeration between particles . In our previous study, cooling and external electric fields were applied to activate the particle growth substantially. Diffusiophoretic and thermophoretic depositions can also be effective for particle capture in the flue gas cooling process .…”
Section: Introductionmentioning
confidence: 99%